Wearable Technology Trials in Cardiac Rehabilitation (International Journal of Scientific Research in Science and Technology, 2025)
This comprehensive review examines the integration of wearable technology into cardiac rehabilitation (CR) programs, synthesizing findings from a diverse range of clinical trials. The analysis reveals that wearable devices significantly enhance exercise capacity and physical activity [1, 7, 12, 15, 16] levels in patients with cardiovascular disease, particularly within remote or home-based rehabilitation models. These technologies address critical barriers to traditional center-based CR, such as geographical distance and accessibility, thereby improving patient participation and adherence [4, 13, 20]. However, the widespread adoption of wearables in clinical CR is not without its challenges [5, 8, 21, 22]. Concerns persist regarding device accuracy, the complexities of data integration into existing healthcare systems, and the need for robust regulatory frameworks. Furthermore, while physical outcomes show consistent improvement, the impact on broader physiological parameters and patient-reported quality of life [2, 19] remains mixed, underscoring the necessity for holistic, multi-component interventions. The future [3, 9, 14] trajectory of wearable-enabled CR points towards increasingly personalized and adaptive programs, leveraging advancements in artificial intelligence and immersive technologies, coupled with evolving policy and reimbursement structures to maximize their clinical utility and reach.